Archiving strategies in the computational age: creating a media + data art digital media library based on a curatorial methodology - Alonso-Calero, José María; Vertedor Romero, José Antonio; Robles-Florido, Juan Carlos (My University, 2022)
As an innovative solution to the challenges of documenting, indexing and researching new media art, this proposal proposes the creation of the Video-Policy media library (from now on MeViPol) within the framework of the research group HUM-1062: Policies of the audio-visual image and its technological environment in artistic practice. This project focuses on two lines of research. On the one hand, curatorial strategies for archiving works developed in Media Art and Data Art. On the other hand, we consider that the artistic trends encompassed in these two blocks have characteristics of obsolescence due to the rapid advance of technology, so MeViPol proposes a virtual space in which both the programming code with which these works are developed and the records generated for their development, both technical and conceptual, is collected.
Keywords: Arte y tecnología; Sistemas interactivos (Informática); Arte - Investigación; Exposiciones; Arte - Bases de datos; Media Art; Data art; Media art; Archive of Art; Curatorial politics; Territoriality; Art research; Otherness; Interactive archive